2018
DOI: 10.3389/fphys.2018.01270
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Dnmt3a1 Transcript Inhibits Adipogenesis

Abstract: DNA (cytosine-5)-methyltransferase 3a (Dnmt3a) is an enzyme that catalyzes the transfer of methyl groups to specific CpG forms in DNA. In mammals, two variant transcripts of Dnmt3a have been successfully identified. To the best of our knowledge, no Dnmt3a transcripts in an avian have been successfully identified. This study was performed to detect different transcripts of Dnmt3a in chickens and to examine whether a novel Dnmt3a transcript named Dnmt3a1 may regulate adipogenesis. In addition to cloning, sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 67 publications
2
14
1
Order By: Relevance
“…Growing number of studies suggested that DNA methylation played significantly role in adipogenesis (Broholm et al, 2016;Chen et al, 2016;Lim et al, 2016). Previous studies recommended that DNMT3A inhibited porcine intramuscular preadipocytes differentiation by changing the methylation levels of p21 and PPARγ (Abdalla et al, 2018;Qimuge et al, 2019). Zhang et al (2014) found that MBD4 inhibited porcine preadipocytes differentiation by changing the DNA methylation levels of adipogenic genes.…”
Section: Introductionmentioning
confidence: 99%
“…Growing number of studies suggested that DNA methylation played significantly role in adipogenesis (Broholm et al, 2016;Chen et al, 2016;Lim et al, 2016). Previous studies recommended that DNMT3A inhibited porcine intramuscular preadipocytes differentiation by changing the methylation levels of p21 and PPARγ (Abdalla et al, 2018;Qimuge et al, 2019). Zhang et al (2014) found that MBD4 inhibited porcine preadipocytes differentiation by changing the DNA methylation levels of adipogenic genes.…”
Section: Introductionmentioning
confidence: 99%
“…Chicken primary preadipocytes were isolated from the abdominal fat tissue of 25-day-old yellow-feathered chicks (Kwangfeng) under sterile conditions as previously reported (Abdalla et al, 2018b). Briefly, the chicks (n = 3) were humanely slaughtered and the abdominal fat tissues (about 3 g) were rapidly excised, placed in a 6-cm petri dish containing 4 ml DMEM/F12 medium (Invitrogen, Carlsbad, United States), and minced into sections of approximately 1 mm 2 using scissors.…”
Section: Primary Preadipocyte Isolation and In Vitro Differentiationmentioning
confidence: 99%
“…The novel transcript detection of Dnmt3a was performed as previously described (Abdalla et al, 2018b). Briefly, PCR amplification and Sanger sequencing methods were used to detect novel splice variants of Dnmt3a.…”
Section: Detection Of Novel Splice Variants Of Dnmt3a Genementioning
confidence: 99%
See 2 more Smart Citations